A survey on patients postoperative pain experience / Yeo King Hong - Yeo, King Hong (2016)
Background, Pain is one of the major concerns of patient undergoing surgery. Unresolved postoperative pain can negatively affect a patien's well-being on many levels. Efforts have been made to address postoperatiove pain. Hovever, throughout the years, studies have shown that moderate to severe postoperative pain is still undermanaged. The aim of this study is to examine the performance of postoperative pain management in UMMC from the patients' perspective. Methods, 150 patients who underwent elective surgery in UMMC were recruited to complete a questionnaire. The questionnaire explored the incidence and everity of postoperative pain, emotional and functional disturbance caused by pain as well as the patients' level of satisfaction towards their pain management. Results, The incidence of moderate to severe pain on P DI wa 52%. Pain wa found to be a ociated with functional and emotional disturbances. Younger age, ASA> 1, and orthopedic surgery were found to be risk factor for moderate to severe pain. The patients were generally satisfied with the pain management given. Conclusions, Acute postoperative pain remains prevalent despite various efforts. Opioids are still the mainstay of treatment for moderate to severe pain, but it undesirable side effect profile limits its usage. A new approach is needed to further improve patients postoperative pain experience.